2004
DOI: 10.1111/j.0886-0440.2004.200306.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Leaflet Preservation During Mitral Valve Replacement:. Modified Anterior Leaflet Preservation Technique

Abstract: Leaflet preserving MVR operation not only improves the left ventricular performance but also reduces the mortality and morbidity after MVR. LVEF increases both at rest and during exercise. Risk of LVOT obstruction can be completely eliminated with our simple technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…Patients with chordal preservation (anterior, posterior, or complete) had superior left ventricular end systolic and diastolic volumes, as well as end-systolic stress and ejection fraction. More recently, these results have been confirmed by Cingoz et al [28] in 94 patients using a complete chordal preservation technique during MVR.…”
Section: Human Echocardiographic (Physiological) Studiessupporting
confidence: 54%
“…Patients with chordal preservation (anterior, posterior, or complete) had superior left ventricular end systolic and diastolic volumes, as well as end-systolic stress and ejection fraction. More recently, these results have been confirmed by Cingoz et al [28] in 94 patients using a complete chordal preservation technique during MVR.…”
Section: Human Echocardiographic (Physiological) Studiessupporting
confidence: 54%
“…In the current analysis, 2 studies [9,10] reported isolated MV repair with a perioperative stroke rate of 3.12% and a summary OR of 9.36, and one study with isolated MVR [11] . The remaining studies involved one or more associated procedures like CABG, maze procedures, or aortic valve procedures depending on the patients' associated symptoms or the surgeons' judgment and restricted further subgroup analyses.…”
Section: Discussionmentioning
confidence: 89%
“…The calculated summary OR was 9.3686 (95% CI 1.302-67.401, p = 0.0263). One primary study [11] involved isolated MVR with a perioperative stroke rate of 1.06%. Majority of MV procedures were performed concurrently with other valvular or coronary artery procedures or atrial fibrillation surgery and this lack of adequate patients undergoing isolated MV procedures limited an extensive analysis of perioperative outcomes.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…However, this issue has not yet been clarified. 12 Both techniques (bileaflet preservation and posteriorleaflet-only preservation) result in significant decreases in LVES and LVED dimensions during the postoperative period. Such a decrease in LV size introduces the possibility, in cases of bileaflet preservation, of contact between subvalvular structures and the mechanical prosthetic valve leaflets, and of consequent LVOT obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of complications associated with bileaflet preservation in the present study, there are many reports of LVOT obstruction and hindered prosthetic-valve-leaflet function. 4,5,12 Bileaflet preservation should be chosen to prevent further decrease in LVEF in patients who present with substantially impaired LV function, on the condition that the technical difficulties and postoperative risks of bileaflet preservation are considered. In this manner, the risk of adverse sequelae to bileaflet preservation can be reduced.…”
Section: Discussionmentioning
confidence: 99%